First report of cervical discospondylitis due to Pseudomona spp. in a puppy patient in Lima, Peru: Case Report - Esparza Juarez, Bianca Cristina (2023)
We present the case of a three-month-old female canine, mixed breed, attended in the city of Lima, Peru, who was diagnosed with discospondylitis due to Pseudomona spp. The canine arrived for consultation presenting fever, decay, prostration and unspecific pain in the neck. A complete hemogram, renal hepatic biochemical profile and a T4 test were performed. In addition, infectious diseases were ruled out by serology, PCR test, parasitology, urine culture and hemoculture. All tests showed negative results except for the hemoculture, where Pseudomona spp. was isolated. Subsequently, X-rays and an MRI were taken. From these tests, a discospondylitis (C4-C5) with mild compressive signs was determined. Hemoculture and antibiogram allowed to apply a treatment according to the definitive diagnosis. After being hospitalized for a week, the canine was partially discharged and followed up for two months. Finally, a favorable evolution was observed.